1979
DOI: 10.1084/jem.149.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of type-specific polysaccharide antigen from group B type Ib streptococci.

Abstract: Lancefield et al.(1) have clearly demonstrated that the capsular polysaccharides of group B streptococci are antigenic and that the antibodies are protective in mice except with type III, where no mouse-virulent strain is available. However, a chicken embryo model has been established for type III and the antibody found to be specifically protective (2). Recently, emphasis has been centered on the isolation and characterization of the capsular antigens from various types (3-8). However, inasmuch as the capsule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…In S. suis, the polysaccharides are readily detached from the cocci by digestion with lysozyme . Group B (14) . In group B streptococci and in S. suis, individual-type polysaccharides are each composed of four or five different sugars (14-16) of which glucose, galactose, N-acetyl glucosamine, and sialic acid are common to all .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In S. suis, the polysaccharides are readily detached from the cocci by digestion with lysozyme . Group B (14) . In group B streptococci and in S. suis, individual-type polysaccharides are each composed of four or five different sugars (14-16) of which glucose, galactose, N-acetyl glucosamine, and sialic acid are common to all .…”
Section: Discussionmentioning
confidence: 99%
“…S. suis type 1 streptococci elicit in pigs antibodies that protect against infection type specifically (5), but this has yet to be confirmed with type 2 . Group B streptococci induce in rabbits antibodies that protect mice type specifically (17) ; some of the group B type-specific polysaccharides appear capable of eliciting antibodies with more than one homologous specificity directed against different parts of the same molecule (14,15) .…”
Section: Discussionmentioning
confidence: 99%
“…
It is widely believed that antibodies to the group B streptococcal (GBS) typespecific polysaccharides are of major importance in human host defenses against GBS infection. All four of the type-specific polysaccharides elicit antibodies against at least two forms of the antigens: a complete antigen that contains Nacetylneuraminic acid (sialic acid) at the nonreducing ends of the side chains and an incomplete or nonsialated antigen (1)(2)(3)(4). This was first demonstrated for the type II polysaccharide by Lancefield and Freimer (1) when they showed that rabbit antisera directed against either the complete or incomplete antigen would protect mice from a lethal challenge of live type II organisms.
…”
mentioning
confidence: 98%
“…All the initially untypable strains that were shown by the screening lectin-agglutination test to contain sialic acid also possessed one of the new polysaccharides. The possibility cannot be excluded that some of the lectin-negative GBS contain an amount of type-polysaccharide antigen undetectable by our methods; one must bear in mind the many factors that influence the synthesis and detectability of type antigens or their components (Wilkinson, 1975;Baker et al, 1976;Kane and Karakawa, 1977;Kasper et al, 1979;Tai et a/., 1979;Doran et al, 1980). In any event, the extended typing scheme substantially reduces the number of N T strains.…”
Section: Discussionmentioning
confidence: 95%